المسائل النحوية وتجلياتها عند العلماء (إن النافية أنموذجاً) (مجلة ديالى للبحوث الانسانية, 2025)
هذه مقالة وصول مفتوح بموجب ترخيصCC BY 4.0 (http://creativecommons.org/licenses/by/4.0/)This research deals with the significance of the faces of  grammatical issues among scholars and we have chosen(that) negation as a model for our research explaining the opinions of scholars in that، in which grammatical issues branched out between agreeing with their work and those contrary to this opinion and the evidence that documents this grammatical presence، A definition of syntax and the benefits of defining it is the significance of aspects related to the work of (In) and the opinion of scholars in that. As for the second topic، it dealt with the work of (In) and the conditions and evidence for its work.        يتناول هذا البحث مغزى وجوه المسائل النحوية عند العلماء وقد اخترنا (إن) النافية أنموذجا لبحثنا موضحين فيه آراء العلماء في ذلك التي تفرعت فيه المسائل النحوية بين موافق لعملها وبين مخالف لهذا الرأي والشواهد التي توثق هذه الوجوه النحوية ، وانقسم البحث الى مبحثين تناول المبحث الاول بعد تعريف للنحو والفوائد من تعريفه مغزى الوجوه المتعلقة بعمل (إن) ورأي العلماء بذلك اما المبحث الثاني فتناول عمل (إن) والشروط والشواهد بعملها بعد ذلك خاتمة نتائج هذا البحث.